2016
DOI: 10.1134/s020228931602016x
|View full text |Cite
|
Sign up to set email alerts
|

Naked singularity formation in generalized Vaidya space-time

Abstract: The gravitational collapse in generalized Vaidya space-time is considered. It is known that the end state of gravitational collapse, as to whether a black hole or a naked singularity is formed, depends on the mass function M (v, r). Here we give conditions for the mass function which correspond to the equation of the state P = αρ. where α ∈ (0, 1/3], and according to these conditions we obtain either a black hole or a naked singularity as the end state of gravitational collapse. We also give the conditions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…The properties of generalized Vaidya spacetime has been studied for the equation of the state P = αρ where α belongs to the interval [0 , 1] in articles [8,9]. If we satisfy this equation of the state then the mass function M(r, v) has the form…”
Section: The Generalized Vaidya Spacetimementioning
confidence: 99%
See 1 more Smart Citation
“…The properties of generalized Vaidya spacetime has been studied for the equation of the state P = αρ where α belongs to the interval [0 , 1] in articles [8,9]. If we satisfy this equation of the state then the mass function M(r, v) has the form…”
Section: The Generalized Vaidya Spacetimementioning
confidence: 99%
“…M. Mkenyley et al investigated the question about the gravitational collapse of generalized Vaidya spacetime [7] and showed that the result of this collapse might be the naked singularity. Furthermore, the conditions for the mass function were obtained [8,9]. Vaidya spacetime is the one of the earliest examples of cosmic censorship conjecture violation [10].…”
Section: Introductionmentioning
confidence: 99%
“…This paper considers gravitational collapse of thin radiating shells (Vertogradov 2016). The first shell collapses at the central singularity at r = υ = 0 where M(0, 0) = 0.…”
Section: The Temporary Naked Singularity In Generalised Vaidya Spacetimementioning
confidence: 99%
“…Let us consider the simplest case, when the equation of the state is ) are the same (Vertogradov 2016).…”
Section: The Temporary Naked Singularity In Generalised Vaidya Spacetimementioning
confidence: 99%
See 1 more Smart Citation